2020
DOI: 10.1097/md.0000000000023052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial genes associated with lung adenocarcinoma by bioinformatic analysis

Abstract: Lung cancer is the world's most common malignancies and ranks first among all cancer-related deaths. Lung adenocarcinoma (LUAD) is the most frequent histological type in lung cancer. Its pathogenesis has not yet been fully elucidated, so it is of great significance to explore related genes for elucidating the molecular mechanism involved in occurrence and development of LUAD. To explore the crucial genes associated with LUAD development and progression, microarray datasets GSE7670, GSE10072, and GSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Etoposide, which targets TOP2A, has been approved for the treatment of small cell lung cancer, but there are currently no drugs for LUAD (48,49). Through various bioinformatics approaches, TOP2A has been identified as an independent factor affecting the prognosis of patients with LUAD (50)(51)(52)(53), whereas an increased TOP2A expression has also been identified as a potential risk factor for pathological stage I LUAD (54). Ciclopirox olamine and quercetin have also been demonstrated to exert tumor-suppressive effects via TOP2A in LUAD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide, which targets TOP2A, has been approved for the treatment of small cell lung cancer, but there are currently no drugs for LUAD (48,49). Through various bioinformatics approaches, TOP2A has been identified as an independent factor affecting the prognosis of patients with LUAD (50)(51)(52)(53), whereas an increased TOP2A expression has also been identified as a potential risk factor for pathological stage I LUAD (54). Ciclopirox olamine and quercetin have also been demonstrated to exert tumor-suppressive effects via TOP2A in LUAD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, tumor cell apoptosis increased. According to various studies, RRM2 can also be used as a target for antilung cancer drugs 28 . IGF2BP3 is a member of the IGF2BPs family, which are consider having a marked impact on cancer occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…According to various studies, RRM2 can also be used as a target for antilung cancer drugs. 28 IGF2BP3 is a member of the IGF2BPs family, which are consider having a marked impact on cancer occurrence and development. Guo et al found that IGF2BP3 was abnormally highly expressed in LUAD and this could lead to a weaker prognosis ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] BUB1B overexpression significantly reduces OS in LUAD patients. [ 28 ] In addition, UBE2C expression is associated with poor LUAD patients’ prognosis undergoing surgery. [ 29 ] In gastric cancer, overexpression of the mitotic checkpoint gene BUB1 is associated with tumor cell proliferation and gastric cancer progression.…”
Section: Discussionmentioning
confidence: 99%